Abnormalities of heart rhythm in newborns - Garrido García Luis Martín (Instituto Nacional de Pediatría, 2014)
Arrhythmias are a variety of cardiac rhythm disturbances that may occur in fetuses and neonates considered healthy. Most of these are benign. The reported incidence fluctuates from 1 to 10% in newborns during the first days after birth. The presence of arrhythmias in the neonatal period involves high morbidity and mortality, particularly when associated with congenital heart disease or lack of response to medical treatment. The appropriate pharmacological control of the abnormal rhythm provides good long-term prognosis. The natural history of arrhythmias in the neonatal period differs impor- tantly from arrhythmias presented in other pediatric age groups. They can be classified as: sinus arrhythmia, tachyarrhythmias, long QT syndrome and bradyarrhythmias. It is important that the physicians responsible for the management of these patients recognize the causes for the development of arrhythmias as well as the diagnostic and therapeutic options available.